2017
DOI: 10.1038/s41598-017-06109-y
|View full text |Cite
|
Sign up to set email alerts
|

Endolysosomal targeting of a clinical chlorin photosensitiser for light-triggered delivery of nano-sized medicines

Abstract: A major problem with many promising nano-sized biotherapeutics including macromolecules is that owing to their size they are subject to cellular uptake via endocytosis, and become entrapped and then degraded within endolysosomes, which can significantly impair their therapeutic efficacy. Photochemical internalisation (PCI) is a technique for inducing cytosolic release of the entrapped agents that harnesses sub-lethal photodynamic therapy (PDT) using a photosensitiser that localises in endolysosomal membranes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…5a-e). This cytoplasmic distribution pattern has been observed for other Ce6-conjugates and nanoparticles 13,25 .…”
Section: Ce6-gvs Are Taken Up By Cancer Cells and Accumulate In Endossupporting
confidence: 75%
“…5a-e). This cytoplasmic distribution pattern has been observed for other Ce6-conjugates and nanoparticles 13,25 .…”
Section: Ce6-gvs Are Taken Up By Cancer Cells and Accumulate In Endossupporting
confidence: 75%
“…Chlorin e 6 is a porphyrin derivative of interest in PDT capable of generating singlet oxygen. By conjugating chlorin e 6 to a cell penetrating peptide, Eggleston et al (Yaghini et al, 2017 ) reported that such porphyrin-like molecules can efficiently be used in PDT and employed in photo-induced cellular internalization, which is a new technology to increase the intracellular delivery and efficacy of nano-sized biotherapeutics. This work opened the way to the use of porphyrins not only as effective near infrared dyes for bioimaging or therapeutic agents but also as promoters of drug delivery (Yaghini et al, 2017 ).…”
Section: Optical Sensing Approaches: the Role Of Oxygen Quenchingmentioning
confidence: 99%
“…Furthermore, sharp Soret and Q bands are observed for Ce6 in protic solvents except for water 14,29 . To improve the poor water solubility of Ce6 for PDT, various kinds of nano-sized drug carriers such as nano-graphene 20 and gold vesicles 21 , or PS-conjugates with polyvinylpyrrolidone (PVP) 24,30,31 , human serum albumin 2 , polymeric micelles 32 , silica 22 , peptides 33 , glucamine (BLC 1010) 34 , and Ce6-conjugates with superparamagnetic iron oxide nanoparticles (SPIONs) by multistep chemical reactions 3537 have been developed. Unfortunately, Ce6’s characteristic PDT properties are often suppressed when incorporated into nanocarriers due to quenching 3841 .…”
Section: Introductionmentioning
confidence: 99%